Antibacterial Activity of Essential Oils of Some Moroccan Aromatic Herbs Against Selected Food-related Bacteria. Issue 5 (3rd July 2016) - El Abdouni Khayari, Mohamed; Jamali, Chaima Alaoui; Kasrati, Ayoub; Hassani, Lahcen; Leach, David; Markouk, Mohammed; Abbad, Abdelaziz
Abstract: The present study evaluates the antibacterial activity of essential oils (EOs) of some widely used Moroccan aromatic herbs namely, Thymus satureioides, Achillea ageratum, Cotula cinerea, Salvia officinalis, and Salvia aucheri subsp. blancoana . The chemical composition was characterized by means of GC-MS and a total of 47 components were identified accounting for more than 96.5% of the total oils. A. ageratum oil was particularly rich in terpene alcohol which included artemisyl acetate (70.1%), yomogi alcohol (12.4%) and artemisia alcohol (7.1%). The T. satureioides EO was characterized by high contents of carvacrol (24.1%), borneol (18.1%), p-cymene (7.0%), camphene (6.8%) and γ-terpinene (6.5%). The C. cinerea EO contained trans -thujone (41.4%), cis -verbenyl acetate (24.7%) and santolina triene (7.2%) as major constituents. S. officinalis EO had a high content of trans -thujone (20.2%), 1, 8-cineole (19.2%), camphor (14.7%), while the S. aucheri subsp. blancoana EO was characterized by camphor (34.7%), followed by camphene (19.9%) and α-pinene (18.7%) as main constituents. EOs were evaluated for antibacterial activity against seven bacteria of significant importance for food hygiene. According to the results, most EOs studied were effective against Gram-positive bacteria with MIC/MBC values of 1.71 mg/mL to 74.32 mg/mL. The greatest effectiveness was achieved with T. satureioides oil (MIC = 2.25-4.50 mg/mL), while the weakest potency was displayed by the A. ageratum EO (MIC = 4.64-74.32 mg/mL). Of the EOs tested, only those obtained from T. satureioides and C. cinerea were able to control the Gram-negative bacteria, with the exception of Pseudomonas aeroginosa .